Influence of Peak Wavelengths on Properties of Mixed-LED White-Light Sources. (16th December 2010) - Soltic, Snjezana; Chalmers, Andrew N.
Abstract : The purpose of this investigation is to quantify the influence of the peak wavelength shifts in commercially available LEDs on the characteristics of the mixed-LED white-light sources. For this purpose, a tetrachromatic spectrum was optimized and then subjected to deviations in the peak wavelengths. A total of 882 combinations of peak wavelength values were evaluated, and the results are reported in terms of correlated colour temperature, colour-rendering properties, and radiant luminous efficacy. The results show that there can be significant changes in the characteristics of the source under these conditions. Such changes are highly likely to present problems when dealing with applications where an effective and accurate white-light source is important.